Controlling in wissenschaftlichen Verlagen ; Analyse IT-induzierter Verèanderungen wissenschaftlicher Verlage und Konzeption ausgewèahlter Controlling-Instrumente - Ortelbach, Bjèorn (Universitèatsverlag Gèottingen, 2007)
Compared with other industries, scientific publishing has a centuries-old tradition. However, it is currently the development of digital information and communication technologies in probably the biggest upheaval since the invention of the printing press. Bjèorn Ortelbach deals with the impact of technological development in the scientific publishing industry from a business point of view. In the first part of the book he analyzes how value added cost structures and business models of publishers change. The second part of the book deals with the impact of these changes on the control of these companies. Based on the previously worked out specifics of the industry design proposals for the use of controlling mechanisms are developed.